Anti Denaturation And Antioxidant Activities Of Annona Cherimola In-Vitro - ADARSH VERMA .M; AJAY KUMAR .P; KAVITHA .D; ANURAG .KB (International Journal of Pharma and Bio Sciences, 2011)
Annona cherimola is believed indigenous to South Central America and also found in some parts of Asia. An attempt is made to evaluate the anti inflammatory and antioxidant activites of Annona cherimola leaf extract as the denaturation of proteins and free radical damage or oxidative stress are inter-linked and influence each other. Invitro anti inflammatory and antioxidant properties were tested on hexane and methanolic leaf extracts of Annona cherimola by means of anti denaturation of bovine serum albumin and reducing antioxidant power respectively. In anti denaturation study it was observed that methanolic extract showed greater percentage of inhibition of bovine serum albumin denaturation i.e 77.6% where as hexane extract showed 63.5% at the lowest concentration respectively. In case of antioxidant screening also, methanolic extract showed better reducing antioxidant power compared to hexane extract dose dependently. Thus the results indicate that methanolic extract of Annona cherimola was found to possess significantly good anti inflammatory and antioxidant activities and this can be attributed to the presence of phenolic compounds